PENGEMBANGAN PERMAINAN KERETA RINTANGAN BAGI ANAK PAUD LABSCHOOL UNNES - Zakaria, Taqwa; Tandiyo Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research discusses the Kereta Rintangan game; for PAUD LABSCHOOL UNNES children; as a form of effort to improve motor skills; rough and cognitive for children. The design of this game takes into account several aspects, such as being educational and fun, and can stimulate creativity, cooperation and problem solving abilities in children. In the development process, the method used is the research and development (R&D) method to produce appropriate products. This obstacle train game involves several physical activities, such as crossing obstacles which have several goals, including training balance, coordination and muscle strength. It is hoped that the results of this development can be a solution for educational game activities, as well as optimizing the development of early childhood. Trial activities that have been carried out at PAUD LABSCHOOL UNNES; shows that the obstacle train game has been accepted by children and also has a positive impact on children's motor skills and social interactions. Children feel happy and play games happily.